Combination Therapy of Momordica charantia Linn. (Bitter Melon) with Antihyperglycemic Agent Gives Increased Antioxidative and Hepatoprotective Actions in Alloxan-induced Diabetic Rats (Bangladesh Pharmaceutical Journal, 2019)
Bitter melon, a popular vegetable of the Asian and African community, is used as an antidiabetic herb for the management of diabetes and its associated complications. The fastest growing metabolic disorder, diabetes mellitus (DM), is now a major cause of morbidity and mortality in developed countries. All the associated complications produced in diabetes are mainly caused by the imbalance between generation of free radicals and the antioxidant systems like catalase (CAT) and super oxide dismutase (SOD) enzymes. Again increased level of serum glutamate pyruvate transaminase (SGPT) and serum glutamate oxaloacetate transaminase (SGOT) are considered a consequence of hepatocyte damage due to non-alcoholic fatty liver disease (NAFLD) and patients with diabetes have an increased risk NAFLD and steatohepatitis. The present study was aimed at evaluating the effects of fixed dose combination therapy of Momordica charantia crude methanolic extract with metformin on oxidative stress and liver dysfunction indices in alloxan-induced diabetic Swiss Albino rats. Various groups of alloxan-induced diabetic rats (AIDRs) were daily treated for four weeks with bitter melon extract (BME) [(300 mg/kg body weight (BW)], metformin [(15 mg/kg body weight (BW)] and their combination dose (150 mg/kg BW + 7.5 mg/kg BW), separately through oral gavage. In our study, we observed that combination therapy lowered SGPT & SGOT level by 34.58% and 47.89%, respectively and increased SOD & CAT enzyme activity by 74.94% and 43.36%, respectively in comparison with their diabetic control groups. The changes obtained from the combination therapy were significantly (p